Dose-escalation study of a second-generation non-ansamycin HSP90 inhibitor, onalespib (AT13387), in combination with imatinib in patients with metastatic gastrointestinal stromal tumour. (July 2016) - Wagner, Andrew J.; Agulnik, Mark; Heinrich, Michael C.; Mahadevan, Daruka; Riedel, Richard F.; von Mehren, Margaret; Trent, Jonathan; Demetri, George D.; Corless, Christopher L.; Yule, Murray; Lyons, John F.; Oganesian, Aram; et al.
Abstract: Background: Gastrointestinal stromal tumours (GIST) treated with the tyrosine kinase inhibitor (TKI) imatinib can become resistant when additional mutations in the receptor tyrosine kinases KIT or PDGFRA block imatinib activity. Mutated KIT requires the molecular chaperone heat-shock protein 90 (HSP90) to maintain stability and activity. Onalespib (AT13387) is a potent non-ansamycin HSP90 inhibitor. We hypothesised that the combination of onalespib and imatinib may be safe and effective in managing TKI-resistant GIST. Patients and methods: In this dose-escalation study, we evaluated the safety and efficacy of combination once-weekly intravenous onalespib for 3 weeks and daily oral imatinib in 28-d cycles. Twenty-six patients with TKI-resistant GIST were enrolled into four sequential dose cohorts of onalespib (dose range, 150–220 mg/m 2 ) and imatinib 400 mg. The relationship between tumour mutational status ( KIT/PDGFRA ) and efficacy of treatment was explored. Results: Common onalespib-related adverse events were diarrhoea (58%), nausea (50%), injection site events (46%), vomiting (39%), fatigue (27%), and muscle spasms (23%). Overall, 81% of patients reported more than one onalespib-related gastrointestinal disorder. Nine patients (35%) had a best response of stable disease, including two patients who had KIT mutations known to be associated with resistance to imatinib and sunitinib. Disease control at 4 months was achieved in five patients (19%), and median progression-free survival was 112 d (95% confidence interval 43–165). One patient with PDGFRA -mutant GIST had a partial response for more than 376 d. Conclusion: The combination of onalespib plus imatinib was well tolerated but exhibited limited antitumour activity as dosed in this TKI-resistant GIST patient population. Trial registration ID:clinicaltrials.gov :NCT01294202 Highlights: This was a phase 1 clinical trial in patients with metastatic tyrosine kinase inhibitor (TKI)-resistant gastrointestinal stromal tumours (GIST). Treatment was a combination of onalespib (a heat-shock protein 90 inhibitor) and imatinib (a TKI). Treatment was well tolerated and toxicities consistent with known safety profiles. Disease control at 4 months was seen in five patients (19%); median progression-free survival was 112 d. One patient with PDGFRA -mutant GIST had a partial response for more than 376 d.